2017
DOI: 10.1159/000479998
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes Derived from Human Bone Marrow Mesenchymal Stem Cells Promote Tumor Growth Through Hedgehog Signaling Pathway

Abstract: Background/Aims: Mesenchymal stem/stromal cells (MSCs) are known to home to sites of tumor microenvironments where they participate in the formation of the tumor microenvironment and to interplay with tumor cells. However, the potential functional effects of MSCs on tumor cell growth are controversial. Here, we, from the view of bone marrow MSC-derived exosomes, study the molecular mechanism of MSCs on the growth of human osteosarcoma and human gastric cancer cells. Methods: MSCs derived from human bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 49 publications
3
103
1
1
Order By: Relevance
“…Sonic Hedgehog (Shh) is a secreted morphogen carried by exosomes that elicits differentiation and patterning in developing tissues [21,22]. Shh is expressed in adult tissue and mediates cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Sonic Hedgehog (Shh) is a secreted morphogen carried by exosomes that elicits differentiation and patterning in developing tissues [21,22]. Shh is expressed in adult tissue and mediates cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 1a under electron microscopy, LEX TGF-β1si was a population of micro-vesicles with 40-100 nm in diameter and was consistent with the typical morphology of exosomes [24]. To determine whether knockdown of TGF-β1 expression in L1210 cells could effectively affect the protein pattern on an exosomal level or not, Western blot analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies identified that exosomes could promote the proliferation and migration of gastric cancer cells via the phosphatidylinositol-3 kinase/Akt, nuclear factor-κB and Hedgehog signaling pathways (11)(12)(13). Through this exosomal regulation, gastric cancer cells may become more prone to invade the serosa and exfoliate into the cavity with increased proliferative and migratory abilities.…”
Section: Exosomes In Peritoneal Dissemination Of Gastric Cancermentioning
confidence: 99%
“…Wang et al (48) suggested that serum exosomal miR-19b-3p and miR-106a-5p were novel potential biomarkers for the detection of gastric cancer. Tokuhisa et al (49) suggested that exosomal miR-21 and miR-1225-5p from peritoneal lavage fluid were upregulated in the later stages of gastric cancer and correlated with serosal invasion, which could potentially predict peritoneal recurrence following curative gastric cancer resection (50). However, it remains unknown whether exosomal miRNAs from serum or peritoneum lavage fluid have adequate sensitivity or specificity to serve as novel tumor makers.…”
Section: Early Detection By Exosomal Mirnasmentioning
confidence: 99%